An examination of the reciprocal and concurrent relations between behavioral and cardiac indicators of acute pain in toddlerhood. Issue 7 (July 2020) - Waxman, Jordana A.; DiLorenzo, Miranda G.; Pillai Riddell, Rebecca R.; Flora, David B.; Schmidt, Louis A.; Garfield, Hartley; Flanders, Dan; Weinberg, Eitan; Savlov, Deena
Abstract : Abstract: The aim of this study was to examine the concurrent and predictive relations between healthy toddlers' pain behavior and cardiac indicators (ie, heart rate [HR] and respiratory sinus arrhythmia [RSA]) during routine vaccinations. Caregiver–infant dyads were part of a longitudinal cohort observed during their 12- and 18-month vaccinations. Behavioral and cardiac data were simultaneously collected for 1-minute preneedle and 3-minutes postneedle. Videotapes were coded for pain behaviors (FLACC; Merkel et al., 1997), and cardiac data were analyzed (HR, RSA) during sequential 30-second epochs. Four separate cross-lagged path models were estimated using data from the 12- (n = 147) and 18-month (n = 122) vaccinations. Across 12- and 18-month vaccinations, predictive within-measure relations were consistent for FLACC, HR, and RSA, reflecting good stability of these pain indicators. Behavioral indicators predicted subsequent HR and RSA within the immediate postneedle period. Both baseline behavior and HR/RSA predicted future pain scores. Concurrent residual relations between behavioral and cardiac indicators were inconsistent across time and indicators. Results suggest that behavioral and cardiac indicators reflect unique aspects of the nociceptive response. As such, multimodal assessment tools should be used and contextualized by child age, cardiac indicator, baseline behavior/physiology, and pain phase. Abstract : Concurrent and cross-lagged relations between behavioral and cardiac indicators of pain were inconsistent in toddlerhood. Potentially different dimensions of pain may be reflected.